Overview of Long Term Experiments in Africa - Bationo, A.; Waswa, Boaz Shaban; Abdou, A.; Bado, B.V.; Bonzi, M.; Iwuafor, E.; Kibunja, C.; Kihara, Job Maguta; Mucheru, M.; Mugendi, D.; Mugwe, J.; Mwale, C.; et al. (Springer, 2012)
The prevailing low food production in sub-Saharan Africa is an issue of great concern especially since Africa south of the Sahara is the only remaining region of the world where per capita food production has remained stagnant. This chapter reviews long-term experiments in Africa in the context of shifting paradigms related to tropical soil fertility management from first external input paradigm right through to the current Integrated Soil Fertility Management (ISFM) approach, which is a culmination of the participatory methods developed along the paradigm shift. Long term experiments (LTE) are an important source of evidence for soil fertility decline and provide crucial datasets for the development of sustainable management practices for tropical land-use systems and the amelioration of global climatic and environmental change impacts. A survey was undertaken to identify some ongoing long-term trials distributed across east, south and western Africa and in different agro-ecological zones. A long-term Experiment was defined as that extending over a period of over 5 years and more. Results from these trials are discussed in detail. Inference has been drawn from these findings and includes the following key findings: a) All long term trials showed yield decline, often with a relatively rapid fall to a low level equilibrium; b) At all sites, there were positive yield responses to one or more nutrients added as mineral fertilizers, which were consistent for the duration of the experiments highlighting the effectiveness of mine-ral fertilizers in increasing yield in arable farming systems in Africa; c) Soil organic matter (SOM) also declines significantly when land is cultivated; d) Prolonged treatments using only inputs of organic matter also showed yield declines, although the positive impact were sustained longer than for inorganic fertilizers alone in most cases; e) Rotational treatments, including sequences with legume crops and fallow periods had lower yield declines than monocultures; f) The best results invariably were those treatments that combined inorganic and organic inputs.